The Parent Mealtime Action Scale revised (PMAS-R): Psychometric characteristics and associations with variables of clinical interest. (1st October 2016) - Hendy, Helen; Harclerode, Whitney; Williams, Keith E.
Abstract: The purpose of the present study was to provide a revised and more psychometrically-examined version of the Parent Mealtime Action Scale (PMAS-R), then to examine how well the PMAS-R subscales explained variance for four variables relevant in clinical settings. Study participants included 238 parents of children referred to a hospital-based feeding program (72.3% male children; mean age = 72.2 months; 80 with autism spectrum disorder, 77 with other special needs, 81 with no special needs). Parents completed questionnaires to report child demographics and diet habits. Parents also used a five-point rating instead of the original three-point rating to report their usage of the 31 PMAS feeding practices. Using five-point ratings, the nine subscales of the PMAS-R demonstrated improved internal reliability and test-retest reliability compared to those published for the original PMAS. ANCOVA indicated that special needs status was the child demographic variable most associated with PMAS-R feeding practices. Hierarchical multiple regression revealed that after controlling for child demographics, the nine PMAS-R subscales explained 26–49% of the variance for four variables of clinical interest (fruit and vegetable consumption, snack consumption, total food variety, and weight status). These variables of clinical interest were most often associated with "permissive" feeding practices including low Daily Fruit and Vegetable (FV) Availability, rarely using Insistence on Eating during meals, often using Many Food Choices, and often using Child-Selected Meals. The present study provides a more psychometrically-sound measure of child feeding practices, documents the association between "permissive feeding" and variables of clinical interest, and identifies specific parent practices included in "permissive feeding".